Syntactic Errors in Minikrimi Translated by Students of German Department Universitas Negeri Malang - Farica Amanda (Universitas Negeri Malang, 2020)
This research aims to describe types of syntactic error and its most dominant type in the translation of Minikrimi by students of the Department of German, Universitas Negeri Malang. The method used in this research is qualitative methode with descriptive research type. The results show that there are 9 (nine) forms of syntactic error in the translation results. The most dominant error was error in using of conjunctions.